Credit Loan Payment Accounting Information System at PT BPR Duta Adiarta Medan - Lestari Nadeak (Journal of Economics and Business (JECOMBI), 2022)
To keep abreast of technological developments, especially computers and achieve competitive advantage, BPR DUTA ADIARTA MEDAN requires a form of presenting information and reports that can be accessed quickly, precisely and accurately to support decision making and improve service to customers who make loans. used is the Observation method carried out by literature study, interview method; design method using Data Flow Diagrams (DFD), structural charts. The results of the research are poured into the Accounting Information System for Credit Loan Payments at BPR DUTA ADIARTA MEDAN. which is expected to provide convenience in processing data and creating reports that can assist BPR DUTA ADIARTA MEDAN in analyzing and making decisions.